FOREIGN TRADE AND COMPARATIVE ADVANTAGES OF AGRARIAN SECTOR OF SERBIA AND SURROUNDING COUNTRIES - Božić, Dragica; Nikolić, Marija (Economics of Agriculture, 2019)
Foreign trade of commodities of total economy of Serbia and countries in the region is characterized by a huge deficit. Small economies, such as these, are marked with significant trade openness that is result of their high import dependence. Agrarian sector has a high share in foreign trade of Serbia and surrounding countries. Surplus in foreign trade exists only in Serbian agrarian sector, while the biggest trade deficit is recorded in Bosnia and Herzegovina, and the lowest level of foreign trade coverage (9%) in agrarian sector of Montenegro. Comparative analysis of competitiveness was conducted on the basis of the revealed comparative advantage index. Comparative advantage in the exchange of agro-food products of Serbia with the world is achieved in ten commodity divisions, and the most significant are: cereals; vegetables and fruits; sugar and honey, and in recent years, tobacco and tobacco products. In countries of the region, there is significantly less number of divisions of agro-food products that are competitive on global market.